The Effect of it Sophistication and User Participation on the Effectiveness of Sipd Usage with Personal Techniques as a Moderating Variable - Kadek Diah Amania Wedhayanti; Ni Putu Sri Harta Mimba (Politeknik Siber Cerdika Internasional, 2025)
The rapid advancement of digital technology and the increasing demand for transparency and accountability in government administration have necessitated comprehensive digital transformation initiatives across Indonesian local governments, with the Regional Government Information System (SIPD) serving as a critical component of bureaucratic reform efforts aimed at enhancing efficiency, transparency, and public service delivery. This [A1] research [A2] aims to analyze the influence of information technology (IT) sophistication and user participation on the effectiveness of the Local Government Information System (SIPD) usage, with personal techniques as a moderating variable. This research employs a quantitative approach with an empirical methodology, conducted on local government agencies in Indonesia that implement SIPD. Data were collected through questionnaire distribution to SIPD users at the Denpasar City Regional Secretariat and analyzed using Moderated Regression Analysis (MRA) technique with SPSS software. The results showed that: (1) information technology sophistication did not have a significant effect on the effectiveness of SIPD usage; (2) user participation had a positive and significant effect on SIPD effectiveness; (3) the influence of IT sophistication on SIPD effectiveness was not significant, even when moderated by personal techniques; and (4) personal techniques significantly moderated the relationship between user participation and SIPD effectiveness despite negative coefficients. This research confirms that the success of SIPD usage is more influenced by user involvement and the moderating factor of personal techniques, while technology sophistication alone does not have a significant influence.